SEJARAH BERDIRINYA VERVOLG SCHOOL KABUPATEN ROKAN HULU TAHUN 1913 – 1940 - Natalia S, Merri; Isjoni, Isjoni; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Education is a very important and always interesting to discuss, because the human personality can be formed only through education. The process of education allows for children to unlock and utilise their potential. Educational products are the nation and civilization, as long as both still exist then the educational process will continue to run. Therefore, it is often said that education is a preparation for life, but also education is a means to fight for the independence of Indonesia. The results of the research explain that the background of the founding of Vervlog School Rokan Hulu can not be separated from Ethical Policy of 1901. At this time it was based on the queen of the Netherlands Wilhelmina Ethical Policy which is known as the Dutch policy of repayment on every Kontler or Dutch government catered for the territory of regency to establish village schools both in Java and outside Java island, including Sumatra. The teachers who teach at this Vervlog School are from indigenous communities. In 1913 there were many children who did not want to go to school for fear of Dutch rule. So the Dutch government needed Upas or Police to find indigenous children who were going to school at Vervlog School and the children would be given a present. There are 5 (five) subjects studied in Vervlog School, they are: reading, writing, arithmetic, geography and memorization. At the beginning of the establishment, 1913-1945, this school was named Vervlog School, since independence in 1945 the school changed its name to Citizenry School, then it was renamed the Center School and after the New Order it became the State Elementary School 001 Rambah.Keywords : History, Vervlog School, Rokan Hulu.